Monitoring ECVET implementation strategies in Europe - (:unkn) unknown (Publications Office of the European Union, 2013)
This third analysis of developments in European credit system for vocational education and training (ECVET) for the period from June 2011 to September 2012 covers the 27 EU Member States, the EFTA countries (Iceland, Liechtenstein, Norway and Switzerland) Croatia and Turkey and a total of 37 different education systems (two in Belgium, and four in the UK). Its main objective is to provide an overview of how countries are progressing towards putting into place the necessary conditions for ECVET. The analysis aims at contributing both to the ECVET evaluation scheduled for 2014 and to the review of achievements of the strategic objectives and short-term deliverables of the Bruges communiqué. It is based mainly on the results of interviews with the ECVET users' group members, which were conducted from July 2012 to September 2012 using a questionnaire shaped by Cedefop. "The analysis shows lack of readiness for full-scale implementation but that countries have progressed in creating the conditions to accommodate to ECVET principles. One marked area of progress is the designation of national contact points (NCP) for ECVET and the 'national teams of ECVET experts', drawing on ECVET-related projects already in place. Countries also seem to be moving toward implementation, increasingly involving practitioners. One of the most common activities is the 'marketing' of ECVET to relevant stakeholders, with several reports of activities directed to the promoting ECVET during 2012." (Hrsg., BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Europäisches Leistungspunktesystem; Lernergebnisorientierung; Europa